Manajemen Perpajakan PT Golden Energy Mines Tbk: Strategi Kepatuhan, Kontrol Risiko, dan Kontribusi Ekonomi Nasional - Angga Anggasmara Putra; Ida Farida Adi Prawira; Memen Kustiawan (MES Management Journal, 2026)
Tax management is a critical aspect of multinational corporate operations, particularly in the mining industry under strict regulatory oversight. This study analyzes the tax management system of PT Golden Energy Mines Tbk (GEMS) using a qualitative case study method based on consolidated financial statements and sustainability reports 2023–2024. Research results demonstrate that GEMS implements a full compliance strategy through a comprehensive self-assessment system, quarterly tax risk evaluation, and effective communication with tax authorities. GEMS' tax contribution reached USD 646.68 million in 2023, significantly contributing to the state's Non-Tax Revenue (PNBP) from the energy and mineral sector. Effective tax management is not merely a regulatory requirement but a strategic mechanism to create shared value for all stakeholders while minimizing tax risks and contingent liabilities. The research recommends strengthening international tax transparency and implementing Country-by-Country Reporting to enhance stakeholder confidence.